Evaluation of Rapid Molecular Viral Load Monitoring with ABBOTT m-PIMATM HIV-1/2 VL - Veronika Juanita Maskito; Agus Susanto Kosasih; Lyana Setiawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
World Health Organization recommends rapid results of Human Immunodeficiency Virus (HIV) viral load by using Point of Care (POC) testing, delivering faster decision-making to prevent transmission and suppress drug resistance and greater likelihood of starting therapy if the clinic provides care and treatment services. The m-PIMATM HIV-1/2VL cartridge is an RT-PCR POC test that detects HIV-1 and HIV-2 RNA viral load, recognizing the conserved-part 5'-UTR of the HIV genome. The standard, Roche Cobas®4800 system HIV-1, targets gag and LTR regions. This study aimed to determine the correlation, sensitivity, and specificity of Abbott m-PIMATM HIV-1/2VL compared to Roche Cobas®4800 system HIV-1. A cross-sectional study at Dharmais Hospital Laboratory. EDTA plasma obtained from 200 HIV patients, consisted of 80 high-viral-load samples (>1000 copies/mL), 80 low-viral-load samples (<1000 copies/mL), and 40 undetectable-viral-load samples (<14.2 copies/mL). Kappa Cohen was used to measure the categorical correlation. Sensitivity and specificity were calculated with diagnostic test. Dharmais Ethic Committee released ethical clearance No.0132/KEPK/IX/2020. The categorical correlation of Abbott m-PIMATM HIV-1/2 VL in determining the group of high or low viral load samples was 0.948 (very strong correlation). The categorical correlation deciding whether the HIV viral load sample was high, low, or undetectable was 0.714 (strong correlation). The categorical sensitivity of Abbott m-PIMATM HIV-1/2 VL compared to Roche Cobas®4800 system HIV-1 in categorizing HIV viral load was 97.5%, specificity of 97.5%. Abbott m-PIMATM HIV-1/2 VL performance in determining HIV RNA viral load group samples has a strong correlation compared to Roche Cobas®4800 system HIV-1. A larger study is required.